Mortality from Burn: An Autopsy Based Study from Nepal - Baral, Madan Prasad; Timsinha, Sidarth (Birat Journal of Health Sciences, 2021)
Introduction: In developing countries like Nepal burn deaths are a major public health problem due to their increased mortality, morbidity and long-term disability. A few clinical studies on burns have been reported from Nepal however, autopsy based studies on burns are limited.Objectives: To study the socio-demographic characteristics of victims of burns and evaluate the cause and magnitude of fatal burn injuries retrospectively.Methodology: A two years retrospective analysis of burn deaths brought for autopsy was conducted from January 2017 to December 2018 in a central level hospital of Nepal.Results: Out of 775 total cases autopsied 38 (4.90%) cases were burn related deaths. The majority of the deaths 17(44.70%) occurred in the age group 21-30 years with a preponderance in females 22(57.89%). Majority of the victims were married females 25(65.78%) and most of them were housewives 14(36.84%). Flame burn 23(60.52%) was the most common cause of all burns. The Total Body Surface Area (TBSA) Burn between 50-69% was observed in majority of the cases 27(71.05%).Most of the victims 15(39.47%) survived over 10 days post injury. Burn incidents were mainly accidental 33(86.84%) in nature followed by suicidal burns 5(13.15%). The main cause of burn death was septicemic shock 16(42.10%) followed by neurogenic shock 10(26.31%).Conclusion: The results of this study show that burns injuries are mostly accidental in nature; therefore, the risks of burn injuries should be rightly addressed and appropriate burn prevention strategies should be developed to reduce the frequency and burn related deaths.